DRESS Syndrome Associated with Liposomal Amphotericin-B in a Kidney Transplant Patient: A Case Report - Charfi, Ons; Hammamia, Syrine B.; Aouinti, Imen; Kaabi, Widd; Kastalli, Sarrah; Daghfous, Riadh; El Aidli, Sihem; Lakhoua, Ghozlane; Zaiem, Ahmed (Current Drug Safety, 2023)
Introduction: Liposomal amphotericin B is a widely used broad-spectrum antifungal drug. It was developed to reduce nephrotoxicity and maximize the therapeutic utility of amphotericin B in the treatment of invasive fungal infections. Drug Rash with Eosinophilia and Systemic Symptoms (DRESS) syndrome is a severe drug-induced hypersensitivity syndrome commonly associated with aromatic antiepileptic drugs. Liposomal amphotericin-B was associated with DRESS syndrome in only one case. Case Report: We report an exceptional case of possible DRESS syndrome associated with liposomal amphotericin B in a 31-year-old male renal transplant recipient. Seventeen days after starting liposomal amphotericin B for visceral leishmaniosis, he developed a skin rash with elevated liver tests. Liposomal amphotericin B was then discontinued. A favourable outcome was slowly observed in one month. Results and Conclusion: This case scored two (possible case) based on the criteria adopted by the European group RegiSCAR. The Naranjo score for liposomal amphotericin B was four (possible).
Keywords: Leishmaniosis